PENERAPAN METODE QIROÁTI DALAM MENGEMBANGKAN MINAT BACA AL-QURÁN KEPADA SISWA DI SEKOLAH DASAR AINUR RAHMA KECAMATAN KANIGARAN KOTA PROBOLINGGO - Sofiani Rizkillah, Nizrina; Khosiah, Nur (LPPM STAI Muhammadiyah Probolinggo, 2024)
Religious education is very important for all human beings, especially as Muslims, we must be able to read the holy book of Islam. There are various methods for reading the Al-Qur'an from year to year, one of which is the Qiroati Method, which is a way to read and understand the Al-Quran. This research uses a descriptive qualitative method, data collection techniques using observation, interviews and documentation. Meanwhile, interactive analysis is a data analysis technique that uses data reduction processes, data presentation, and drawing conclusions. The reading method with Qiro'ati must be someone who is Qiro'ati certified, the model used is classical teaching tools, the material contained in the Qiroati book is volumes 1-6. The results of this research show that the Qiroati method uses the rules of reading directly without ejaculation, namely Smooth, fast, accurate, correct and acidic, the Qiro'ati method can develop interest in reading the Koran in elementary school students